STUDI ETNOGRAFI KOMUNIKASI ANTARBUDAYA SUKU BUGIS DI DESA KURAU, BANGKA TENGAH - Rikhansa, Nadhifa; Sjoraida, Diah Fatma; Budiana, Heru Ryanto (Universitas Negeri Malang, 2024)
AN ETHNOGRAPHIC STUDY OF BUGIS INTERCULTURAL COMMUNICATION IN KURAU VILLAGE, CENTRAL BANGKA Desa Kurau, located in Bangka Tengah Regency, Bangka Belitung Islands Province, has been inhabited by the Bugis community since the 1960s. As the second largest ethnic group after the Malays, the Bugis community coexists with the majority Malay population, adapting their cultural practices accordingly. This study aims to analyze communication patterns between Bugis and Malay communities in Desa Kurau using a qualitative approach through communication ethnography. The research findings indicate that transactional communication dominates interactions in Desa Kurau. This includes transcendent communication in religious rituals, interpersonal communication in marriages, and group communication during communal activities. The communication patterns of Bugis communities in Desa Kurau are heavily influenced by their cultural values and history. Bugis Bone and Wajo communities exhibit communication patterns emphasizing cooperation and equality within their groups, using distinct cultural language and symbols. Meanwhile, communication between Bugis and Bangka Malay communities shows dynamic cultural and linguistic adaptations to maintain harmonious relationships. To enhance harmony and cooperation, it is recommended that local government and educational institutions develop intercultural communication education programs and strengthen community discussion forums involving community leaders from both ethnic groups. Desa Kurau, yang terletak di Kabupaten Bangka Tengah, Provinsi Kepulauan Bangka Belitung, telah dihuni oleh Suku Bugis sejak tahun 1960-an. Sebagai kelompok etnis terbesar kedua setelah Suku Melayu, komunitas Bugis hidup berdampingan dengan mayoritas penduduk Melayu dan menyesuaikan praktik budaya mereka. Penelitian ini bertujuan untuk menganalisis pola komunikasi antara masyarakat Bugis dan Melayu di Desa Kurau tersebut menggunakan pendekatan kualitatif melalui metode etnografi komunikasi. Hasil penelitian menunjukkan bahwa komunikasi transaksional mendominasi interaksi di Desa Kurau. Bentuk komunikasi ini meliputi komunikasi transendental dalam ritual keagamaan, komunikasi antarpribadi dalam pernikahan, dan komunikasi kelompok dalam gotong royong. Pola komunikasi masyarakat Bugis di Desa Kurau sangat dipengaruhi oleh nilai budaya dan sejarah mereka. Masyarakat Bugis Bone dan Wajo menunjukkan pola komunikasi yang menekankan kerjasama dan kesetaraan dalam kelompok, menggunakan bahasa dan simbol budaya yang khas. Sementara itu, komunikasi antara masyarakat Bugis dan Melayu Bangka menunjukkan adanya adaptasi budaya dan bahasa yang dinamis untuk mempertahankan hubungan harmonis. Untuk meningkatkan harmoni dan kerjasama, disarankan agar pemerintah daerah dan lembaga pendidikan setempat mengembangkan program pendidikan komunikasi antarbudaya, serta menguatkan forum-forum diskusi komunitas yang melibatkan tokoh masyarakat dari kedua kelompok etnis.